CONTRASTS 21C : People & Places Vietnam, Laos & Cambodia - Caplan, Bill (Faringdon : Libri Publishing, 2018)
Contrasts21c is a photo essay about people and places in Vietnam, Laos and Cambodia thathopes to bring attention to the cultural diversity of this region and itschallenges. The warmth of the people they met, their adaptability and spiritare what inspired this book.
Keywords: Caplan, Bill. -- photographer; Vietnam -- Pictorial works; Laos -- Pictorial works; Pictorial works